PENYELESAIAN ANALISIS YURIDIS PERTANGGUNG JAWABAN PPAT ATAS AKTA JUAL BELI YANG MENGANDUNG UNSUR PERBUATAN MELAWAN HUKUM (STUDI KASUS PUTUSAN PENGADILAN NEGERI SAMPIT NOMOR08/Pdt.G/2020/PN.Spt) - Mohammad Farid; Rumainur (JOURNAL OF LAW AND NATION, 2025)
This research aims to analyze juridically the responsibility of Land Deed Drafting Officials (PPAT) in making Sale and Purchase Deeds (AJB) which contain elements of unlawful acts. This study refers to the case recorded in the Sampit District Court Decision Number 08/Pdt.G/2020/PN.Spt. This case involves PPAT which is considered responsible for the AJB it made even though there are elements of unlawful acts, which have the potential to harm other parties. This research uses a normative research method with a case study approach. In this study, it was found that PPAT has an obligation to ensure the validity of the transaction object and ensure that there are no legal violations in the AJB creation process. The results of the analysis show that even though the PPAT acts as the legal party in making the deed, it can still be held responsible if there is evidence that the deed made contains elements of unlawful acts, whether in the form of fraud, falsification of documents, or transactions that are contrary to applicable legal provisions. Therefore, PPAT must be more careful in carrying out its duties so as not to be involved in actions that violate the law. This research provides recommendations for the need to increase supervision and training for PPAT to prevent similar things from happening in the future.